DInSAR Analysis of Ground Deformation Induced by the 2023 Al Haouz Earthquake, Morocco - A. Habib; I. Berrada; A. El Adnani; Y. A. Laaziz; A. Fadili; A. Lagnaoui; A. Lagnaoui; A. Najih; T. Y. Arrad (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The study investigates the co-seismic ground deformation induced by the Mw 7.2 Al Haouz earthquake that occurred on September 8, 2023, in the Al Haouz region of Morocco. The research employs Differential Interferometric Synthetic Aperture Radar (DInSAR) analysis of Sentinel-1A satellite images acquired before and after the mainshock to map co-seismic deformation patterns and estimate displacement fields. Through this approach, distinct fringe patterns were revealed, indicating significant crustal deformation, with a maximum uplift of approximately 24 cm in the line-of-sight (LOS) direction near the epicenter. Notably, incomplete fringes indicating subsidence were observed in both the northern and southern portions of the fringe lobe, with an associated displacement of approximately 5 cm. The deformation pattern is consistent with a thrust fault mechanism along an ENE-trending reverse fault, forming a horst-pop-up structure. Our findings provide significant insights into the seismogenic fault system and regional tectonics, improving our understanding of earthquake mechanics in this intraplate context and demonstrating the effectiveness of DInSAR in capturing detailed snapshots of co-seismic deformation associated with the devastating event. Additionally, these results have important implications for seismic hazard assessment and disaster risk reduction in Morocco's tectonically active regions.